Rapid sample delivery for megahertz serial crystallography at X-ray FELs. (2018) - Wiedorn, Max O.; Awel, Salah; Morgan, Andrew J.; Ayyer, Kartik; Gevorkov, Yaroslav; Fleckenstein, Holger
No abstract available